The diversity of ‘kristal’ guava (Psidium guajava) fruit quality in response to different altitudes and cultural practices - Neni Musyarofah; Slamet Susanto; Sandra Arifin Aziz; Ketty Sukety; Dadang DADANG (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Musyarofah N, Susanto S, Aziz SA, Suketi K, Dadang. 2020. The diversity of ‘kristal’ guava (Psidium guajava) fruit quality in response to different altitudes and cultural practices. Biodiversitas 21: 3310-3316. The current study aimed to compare the quality of ‘kristal’ guava fruit harvested from different altitudes under different cultural practices. The study was conducted from January to March 2019. Four treatments were examined, i.e., fruit from low altitude-intensive cultural (LI), low altitude-less intensive cultural (LI), middle altitude-intensive cultural (MI), and middle altitude-less intensive cultural (ML). All treatments were arranged in a completed randomized design and each treatment had five trees as replicates The findings of the study showed that there was a variation of fruit quality in response to different altitudes and cultural practices. The fruits harvested from low altitudes were significantly bigger and heavier than the fruits harvested from middle altitude, irrespective of cultural practices. With regard to fruit softness, the fruits from middle altitudes were crispier than fruits from the low altitude. The chemical qualities of the fruits, indicated by TSS/TA ratio and vitamin C, were better in guava orchard under intensive cultural practice than less intensive cultural practice. The intensive cultural practice also improved the guava fruit size as compared to the less intensive cultural practice. This finding may be attributed to pruning which is performed in intensive cultural practice. More beneficial metabolites for human health such as vitamin E and caryophyllene were found in fruit from low altitude.